Endoscopic submucosal dissection versus surgery in elderly patients with early gastric cancer of relative indication for endoscopic resection. Issue 3 (16th September 2021) - Kishida, Yoshihiro; Takizawa, Kohei; Kakushima, Naomi; Kawata, Noboru; Yoshida, Masao; Yabuuchi, Yohei; Yamamoto, Yoichi; Ito, Sayo; Imai, Kenichiro; Hotta, Kinichi; Ishiwatari, Hirotoshi; Matsubayashi, Hiroyuki; et al.
Abstract : Objectives: Surgery is recommended for early gastric cancer (EGC) beyond the endoscopic resection (ER)‐indication for the risk of lymph node metastasis; however, ER may be chosen as a "relative ER‐indication" considering age and comorbidities. This study aimed to compare outcomes of endoscopic submucosal dissection (ESD) only and surgery (primary surgery and additional surgery after non‐curative ESD) among elderly patients with relative ER‐indication EGC and to further assess prognostic factors. Methods: Outcomes of ESD and surgery (417 cases; 114 ESD, 303 surgery) in elderly patients (≥75 years) with relative ER‐indication EGC were retrospectively analyzed. Prognostic factors were also examined. Results: During the observation period (median; ESD, 34 months; surgery, 61 months), 29% of ESD and 35% of surgery patients died, including 4% and 5% from gastric cancer (GC), respectively. ESD showed lower overall survival (OS) than surgery ( P = 0.027) but comparable disease‐free survival ( P = 0.916). OS‐associated factors were age and prognostic nutritional index (PNI) in males (age ≥79, hazard ratio [HR] 2.21, P = 0.001; PNI <45, HR 2.06, P = 0.031) and age in females (age ≥82, HR 4.06, P = 0.004). Treatment was not a prognostic factor in either subgroup. Pathological category ≥pT1b2 (submucosal invasion ≥500 µm) and lymphovascular invasion (LVI) were significantly associated with GC death (mortality: ≥pT1b2, 7.7%, P = 0.002; LVI, 10.1%, P < 0.001). Conclusions: In elderly patients with relative ER‐indication EGC, ESD may have comparable long‐term efficacy to surgery, and treatment selection had a minor contribution to OS. For patients with poor preoperative prognostic factors, diagnostic ESD may be performed first, followed by additional surgery based on pathological results.